COMPARISON BETWEEN TRADITIONAL IT INFRASTRUCTUREAND CLOUD SERVICE MODELS – TECHNOLOGICAL,ECONOMIC, AND OPERATIONAL ASPECTS - Valcheva, Desislava; Andreev, Evgeni (E-Journal VFU, 2025)
Cloud technologies provide computing resources and services via the Internet, such as data storage, software usage, and computing power. They are flexible, scalable, and accessible, allowing users to pay only for what they use. The aim of this article is to conduct a comparative analysis of the advantages and disadvantages of using on-premises infrastructure and cloud service models. The criteria selected for the analysis include costs, maintenance, scalability, accessibility, security, and data control in both environments. The results of the study demonstrate the increasing adoption of cloud services by businesses.